2017
DOI: 10.4317/jced.53888
|View full text |Cite
|
Sign up to set email alerts
|

Extraskeletal myxoid chondrosarcoma of the masticator space in a pediatric patient

Abstract: Extraskeletal myxoid chondrosarcoma (EMC) is a malignant soft-tissue neoplasm rarely described in the head and neck region of children and adolescents. We describe a case of EMC affecting the masticator space and a literature review. A 13-year-old boy who presented a large painless, diffuse mass causing progressive midfacial asymmetry of 6 months duration. Histopathological evaluation revealed a multinodular lesion, containing scattered round vacuolated tumor cells dispersed in an abundant myxoid stroma, separ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Approximately 20% of the cases are located in the trunk, mainly in skeletal muscles, tendons and the deep subcutis; a few cases involve the skin and bone tissue, whereas rare sites include the vulva and the breast [ 5 , 6 ]. After we retrospect 48 cases from 1981–2022 which took place in the head and neck region [ 1 , 7 ], we found that males account for 60.4%( n = 29), while females make up 37.5%( n = 18), and 2.1%( n = 1 case) was unavailable, the male-to-female ratio of about 1.5:1 (Fig. 5 A).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Approximately 20% of the cases are located in the trunk, mainly in skeletal muscles, tendons and the deep subcutis; a few cases involve the skin and bone tissue, whereas rare sites include the vulva and the breast [ 5 , 6 ]. After we retrospect 48 cases from 1981–2022 which took place in the head and neck region [ 1 , 7 ], we found that males account for 60.4%( n = 29), while females make up 37.5%( n = 18), and 2.1%( n = 1 case) was unavailable, the male-to-female ratio of about 1.5:1 (Fig. 5 A).…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of EMC remains controversial. Surgical or accidental trauma may be key factors, along with the inhalation of chemical carcinogens such as hydrocarbons [ 1 , 7 ]. Our patient did not report any intraoral region trauma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations